2017
DOI: 10.24136/eq.v12i4.39
|View full text |Cite
|
Sign up to set email alerts
|

Firm's default ? new methodological approach and preliminary evidence from Poland

Abstract: Research background: Bankruptcy literature is populated with scores of (econometric) models ranging from Altman’s Z-score, Ohlson’s O-score, Zmijewski’s probit model to k-nearest neighbors, classification trees, support vector machines, mathematical programming, evolutionary algorithms or neural networks, all designed to predict financial distress with highest precision. We believe corporate default is also an important research topic to be identified with the prediction accuracy only. Despite the wealth of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The methodology of investigating internal financial risk indicators for enterprises is the coefficient method (Hosaka, 2019;Antunes et al, 2017;Kliestik et al, 2015;Berent et al, 2017;Kovacova & Kliestik, 2017), the essence of which is to conduct enterprise financial analysis. The coefficient methods provide a comprehensive analysis of the financial status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The methodology of investigating internal financial risk indicators for enterprises is the coefficient method (Hosaka, 2019;Antunes et al, 2017;Kliestik et al, 2015;Berent et al, 2017;Kovacova & Kliestik, 2017), the essence of which is to conduct enterprise financial analysis. The coefficient methods provide a comprehensive analysis of the financial status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further seminal work in this field was conducted byShumway (2001), who demonstrated the superiority of the hazard model approach in predicting business defaults over the static approach model (i.e., not considering the multi-period nature of the data). The superiority of the hazard approach has also been confirmed by other authors, such as Chava & Jarrow (2004) andBerent et al (2017). According toGupta et al (2015), 'the discrete hazard modelling technique is well suited to analyse data that consists of binary dependent variables and exhibits both time-series and cross-sectional characteristics, such as bankruptcy data'.…”
mentioning
confidence: 77%
“…The Cox semiparametric proportional model approach was employed to derive the model, it was first adopted by Lando (1998), who was the first to model default using the Cox model. Shumway (2001), Chava and Jarrow (2004), and Berent et al (2017) demonstrated the superiority of the hazard model approach in predicting business defaults over other approaches. Berent et al (2017) highlighted the need for treating the default as a multiperiod process, which advocates the employment of Cox's hazard model approach.…”
Section: Methodsmentioning
confidence: 99%
“…Shumway (2001), Chava and Jarrow (2004), and Berent et al (2017) demonstrated the superiority of the hazard model approach in predicting business defaults over other approaches. Berent et al (2017) highlighted the need for treating the default as a multiperiod process, which advocates the employment of Cox's hazard model approach. According to Gupta et al (2015), the discrete hazard modelling technique is well suited for analysing bankruptcy data as it consists of binary dependent variables and exhibits both, time-series and cross-sectional characteristics.…”
Section: Methodsmentioning
confidence: 99%